2015
DOI: 10.2495/cc150241
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characteristics of port dredging sediments and of the brick slip used in the manufacture of bricks: a comparative study

Abstract: The dredging practices are a major challenge for the development and maintenance of port activities. Millions of cubic meters are extracted regularly from Algerian ports, it is necessary to value them. This study focuses on the development of marine sediments from the port of Bethioua for making bricks. A physicochemical, mineralogical and fine microscopic characterization was done with great care for these marine sediments and for the slip brick at several laboratories in our university (USTO-MB). The physico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Composition of raw mixtures for ceramic materials has an influence on the sintering temperature and final properties of the produced material (Dondi, 2003;Cultrone et al, 2004). Mineralogical studies on fine-grained dredged harbor sediment (Hamer and Karius, 2002;Mezencevova et al, 2012;Benyerou et al, 2015) or river material (Manap et al, 2016) have shown that silt carried in suspension can be valuable material for the ceramic industry based on appropriate grain-size distribution and significant content in clay minerals combined with quartz and some carbonates (Xu et al, 2014;Cappuyns et al, 2015;Haurine, 2015, Haurine et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Composition of raw mixtures for ceramic materials has an influence on the sintering temperature and final properties of the produced material (Dondi, 2003;Cultrone et al, 2004). Mineralogical studies on fine-grained dredged harbor sediment (Hamer and Karius, 2002;Mezencevova et al, 2012;Benyerou et al, 2015) or river material (Manap et al, 2016) have shown that silt carried in suspension can be valuable material for the ceramic industry based on appropriate grain-size distribution and significant content in clay minerals combined with quartz and some carbonates (Xu et al, 2014;Cappuyns et al, 2015;Haurine, 2015, Haurine et al, 2016.…”
Section: Introductionmentioning
confidence: 99%